EXPLORATION OF TRUST PARADOX IN CONSUMER BEHAVIOR IN THE USE OF THE TOKOPEDIA APPLICATION - Suliha, Suliha; Brahmana, Rico; Rachmadi, Firman; Putri, Amelia Delfina; Aulia, Virdha Rahma (PT. Altin Riset Publishing, 2025)
This study explores the Trust Paradox phenomenon among Tokopedia users, a condition where consumers still intend to buy even though their level of trust in the platform is low. Using a quantitative approach and PLS-SEM analysis of 154 respondents, it was found that Perceived Value, User Experience, and Trust Paradox have a significant effect on Purchase Intention. In contrast, Trust and Perceived Risk do not show a significant direct effect. Exploratory analysis identifies user segments with high purchase intentions despite having low trust, strengthening the existence of the Trust Paradox in digital consumer behavior.